التحليل الاستراتيجي للدخل التشغيلي "مدخل تحليل الموارد" دراسة تطبيقية - محمدعلي نصيف جاسم (Journal of Economics and Administrative Sciences, 2010)
Abstract This study dealt with " The Strategic analysis of Operating Income". The study Concerned with two main variables, they are: Strategic analysis and operating income and used one of the total strategic analysis tools, it is "resources analysis method" through analysing the change in operating income in the years that taken in comparing in three components: growth, price recovery and productivity. To achieve the goal of the research, the study depended upon a hypothesis, "The strategic analysis of operating income leads to supply the appropriate information for the management to make sure of executing its definite strategies". There is agroup of aims that this research wanted to achieve, some of them, Increasing the level of understanding of economic units for the importance of strategies, and highlighting the nature of essential role that may be performed by the strategic analysis of operating income. The research was ended with some conclusions that may strategic analysis of operating income contribute in incrasing the information to management.